INTERACTIVE EDUCATIONAL METHODS USED IN TEACHING MEDICAL BIOLOGY AND GENERAL GENETICS IN MEDICAL UNIVERSITIES (Scientific journal of the Fergana State University, 2024)
Currently, our developing country in the form of interactive teaching and learning methods will promote more research on the science of teaching, theoretical and practical analysis of the scientific level. The advantages of interactive methods used in teaching medical biology and general genetics in medical universities are revealed, and interactive educational methods in the study of medical biology and general genetics in medical universities are highlighted, in which interactive teaching methods include exercises and The topics section highlights the achievements of the “Brain Brain” methods assault", "Discussion" and "Problem situation", as well as modern requirements for the educational process.